AVALIAÇÃO DOS PARÂMETROS FÍSICO-QUÍMICOS E DO TEOR DE METAIS EM AMOSTRAS DE SEDIMENTO DE UMA MICROBACIA GAÚCHA - Antunes, M.; Dillon, D. B.; Crespo, J. S.; Giovanela, M. (Geochimica Brasiliensis, 2012)